The tadpole and karyotype of Rhinella (Bufo) achavali (Anura: Bufonidae) - Kolenc, Francisco (2013)
We describe the external morphology, buccal cavity, chondrocranium, hyobranchial skeleton and musculature of the tadpole of R. achavali, along with its karyotype. Tadpoles were found in a permanent streamlet, showing schooling behavior. External larval morphology seems to be much conserved in Rhinella, not helping in the characterization of the proposed species groups. Buccal cavity morphology confirms the distinctiveness of the R. veraguensis group with respect to other known Rhinella. Musculoskeletal characters show most features shared with other Bufonidae, except for some typical of the basal genus Melanophryniscus. Karyotype is composed of 22 biarmed chromosomes, with secondary constrictions in pair 7, like the other species in the R. marina group.